Visual participatory approach to violent behaviour amongst Zimbabwean students: forms and prevalence - Gudyanga, Ephias; Matamba, Nomsa; Gudyanga, Anna (Canadian Center of Science and Education, 2016)
This study investigated the perceptions of students on forms and prevalence of violent behavior in Gweru urban district of Zimbabwe. Visual participatory methodology premised on both qualitative and quantitative paradigms was used. Drawings with focus group discussions were the main data collecting instruments. Participants were fifteen conveniently selected students attending a typical urban high school (females = 7, age range 15-17, males = 8, age range 14-18). Data on forms and prevalence of violence were collected from the students. The majority of the participants portrayed physical violence, vandalism and sexual harassment. It was recommended that schools must develop clear policies in an endeavor to reduce or eliminate violence. Schools Psychological Services must provide psychotherapy to individuals concerned. Visual participatory methodology, a new body of knowledge in Zimbabwe, is a vital tool for future researchers.